Survey on the approaches based geometric information for 3D face landmarks detection. Issue 8 (22nd May 2019) - Manal, El Rhazi; Arsalane, Zarghili; Aicha, Majda
Abstract : Facial landmarks detection is an important and basic step in many face analysis applications. For this reason, it is considered a challenging task as the final results of the analysis depend on the accuracy of the landmarks detection. Decades of research have investigated approaches for two‐dimensional (2D) facial landmarks detection but; however, the good obtained results, they still suffer from some weakness regarding the pose and illumination variations. Recently, the large availability of 3D scans makes the use of 3D face models easier hence, overcome the problems caused using 2D images. Many papers have studied the problem of 3D facial landmarks detection; nevertheless, there is a lack of literature reviews allowing an overview of the studies and researches related to the 3D face landmarks detection. In this study, the authors present a detailed survey of the latest (2010–2018) approaches based geometric information for 3D face landmarks detection, including the limitations and strengths of each work.